1981
DOI: 10.1039/p19810001520
|View full text |Cite
|
Sign up to set email alerts
|

A versatile new synthesis of quinolines and related fused pyridines, Part 5. The synthesis of 2-chloroquinoline-3-carbaldehydes

Abstract: Acetanilides are converted into 2-chloroquinoline-3-carbaldehydes in good yield by the action of Vilsmeier's reagent in phosphoryl chloride solution. The reaction is shown to involve successive conversion of the acetanilide into an imidoyl chloride and then an N-(or-chloroviny1)aniline. The latter enamine is diformylated at its P-position and subsequently cyclised to the chloroquinolinecarbaldehyde. The diformylated intermediates may be isolated in several cases and separately cyclised with polyphosphoric acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
127
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(130 citation statements)
references
References 2 publications
3
127
0
Order By: Relevance
“…29 Reaction of 1a with hydrazine produced a hydrazone which could not be cyclised by refluxing in ethanol. We concluded that the hydrazone had E geometry and thus was sterically prevented from attacking the quinoline C-2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…29 Reaction of 1a with hydrazine produced a hydrazone which could not be cyclised by refluxing in ethanol. We concluded that the hydrazone had E geometry and thus was sterically prevented from attacking the quinoline C-2.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, and partly because of the ready availability of 2-chloro-3-formylquinolines from Meth-Cohn's convenient and efficient synthesis of such molecules from acetanilides and the Vilsmeier reagent, 29 most work has involved these chloro-aldehydes, though these are easily converted into corresponding ketones by Grignard addition then oxidation of the resulting alcohol. 24,30 The reaction of such ketones with hydrazine or arylhydrazines produces 3-substituted 1H-pyrazolo [3,4-b]quinolines simply by refluxing in methanol (Scheme 3); 24,30 it was suggested 30 that the size of the ketone substituent favours formation of the Z-stereoisomer of a first-formed hydrazone, thus having the geometry required for a subsequent ring-closing displacement of the chloride.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, in continuation of research work on developing new quinoline containing heterocycles due to their significant biological activities, it appeared expedient to synthesize a series of condensed and appropriately funtionalised 2-hydrazino[1,3,4]thiadiazepino [7,6-b]quinolines in the present study. The starting compound 2-chloro-3-formyl quinolines, (1a-h) were prepared according to the literature method 29 The 2-hydrazino-[1,3,4]thiadiazepino [7,6-b]quinoline (2a-h) were obtained in one pot by the cyclisation of 2-chloro-3-formylquinolines with carbidimide in presence of p-TsOH catalyst and DMF under microwave irradiation in good yields. This method provides high yield of products in 5-6 min making it a useful method for the synthesis of condensed thiadiazepino quinolines.…”
Section: Resultsmentioning
confidence: 99%
“…The chlorination of compounds (11,12) with SOCl 2 in dry benzene afforded intermediates 3-(chloromethyl)-2-chloroquinoline (17,18) and their successive nucleophilic substitution reaction with sulphanilamide or p-aminophenol in absolute ethanol in the presence of organic base triethylamine (TEA) gave 2-chloroquinolinyl amines (19)(20)(21)(22). While various 1 H-benzimidazol-2-ylsulfanyl)methyl (23)(24)(25)(26) derivatives were prepared by reacting intermediate (17,18) with 2-mercaptobenzimidazole or 2-mercapto-6-nitrobenzimidazole in ethanol in presence of base NaOH.…”
Section: Antimicrobial Screeningmentioning
confidence: 99%